APLIKASI PENJADWALAN MATA PELAJARAN PADA RAUSAN SCIENCE CLUB - Dukhaan Awakhir (2020)
In the era of rapidly developing technological developments, the speed of receiving information is needed in various fields. Rausan Science Club is a learning institution integrated with SMP Negeri 255 Jakarta. The problem that often arises is in scheduling, Rausan Science Club still does it traditionally plus the scheduling system still has some errors. Errors in scheduling make the performance of Rausan Science Club as a learning agency inefficient. For this reason, an application is needed to determine the schedule at Rausan Science Club. The application aims to facilitate scheduling activities that can support and assist learning activities. This study aims to build scheduling applications in the form of computer-based applications for scheduling activities at Rausan Science Club. Application development in this study uses a prototyping method consisting of 3 stages, Listen to customer (requirements gathering), Build / receive mock-ups, Customer test drives mock-ups. In developing the application using PHP as a programming language and MySQL as a Database Management System (DBMS). The design implements the OOAD (Object Analysis and Design) method with Unified Model Language (UML) tools. The expected outcome is the Rausan Science Club scheduling system. The system is expected to make it easier to see the lesson schedule, change lesson schedules, and arrange lesson schedules for the parties concerned.